Math, asked by nisikasharma095, 3 months ago

please give a answer of this question​

Attachments:

Answers

Answered by bhumiraj1234
1

answer is in the attachment

Attachments:
Answered by lalnunkimahmarjoute
0

a =  \frac{ \sqrt{3}  +  \sqrt{2} }{ \sqrt{3} -  \sqrt{2}  }  \: and \: b =  \frac{ \sqrt{3}  -  \sqrt{2} }{ \sqrt{3}  +  \sqrt{2} }

a =  \frac{ \sqrt{3}  +  \sqrt{2} }{ \sqrt{3}  -  \sqrt{2} }  \times  \frac{ \sqrt{3}  +  \sqrt{2} }{ \sqrt{3}  +  \sqrt{2} }

 \:  \:  \:  \:  \:  \:  \:  = \frac{ {( \sqrt{3}   +   \sqrt{2} )}^{2} }{3 - 2}

 \:  \:  \:  \:  \:  = 3  + 2 \sqrt{6}  + 2

\:  \:  \:  \:  \:  = 5 + 2 \sqrt{6}

b  =  \frac{ \sqrt{3}  -  \sqrt{2} }{ \sqrt{3}  +  \sqrt{2} }  \times  \frac{ \sqrt{3} -  \sqrt{2}  }{ \sqrt{3} -  \sqrt{2}  }

\:  \:  \:  \:  \:  =  \frac{ {( \sqrt{3}  -  \sqrt{2}) }^{2} }{3 - 2}

\:  \:  \:  \:  \:  = 3 - 2 \sqrt{6 }  + 2

\:  \:  \:  \:  \:  = 5 - 2 \sqrt{6}

 {a }^{2}  +  {b}^{2}  =  {(5 + 2 \sqrt{6} )}^{2}  +  {(5 - 2 \sqrt{6} )}^{2}

\:  \:  \:  \:  \: \:  \:  \:  \:  \:  = 25 + 2.5.2 \sqrt{6}  + 24 + 25 - 2.5.2 \sqrt{6}  + 24

\:  \:  \:  \:  \: \:  \:  \:  \:  \:  = 2(25 + 24)

\:  \:  \:  \:  \: \:  \:  \:  \:  \:  = 2 \times 49

\:  \:  \:  \:  \: \:  \:  \:  \:  \:  = 98

Similar questions